Adsorption of Basic Yellow 28 in Aqueous Solution by Activated Carbon - Sy Duc, Dao; Bin, Nguyen; Thi Huyen Trang, Tran (Asian Journal of Chemistry, 2012)
In this study, the coal-based granular activated carbon from Ha Bac (GAC-HB) was used to remove basic yellow 28 (BY 28) from aqueous solution. The structure and surface properties of granular activated carbon from Ha Bac were analyzed by modern methods. Its adsorption capacity was also determined by Langmuir and Freundlich isotherms. Effects of some key operating parameters such as the initial dye concentration, contact time, pH as well as the dose of granular activated carbon from Ha Bac on the dye removal were investigated. The results show that the granular activated carbon from Ha Bac is a good adsorbent for removing basic yellow 28.